How to embroider almost every cute thing : a sourcebook of 550 motifs + beginner stitch tutorials - Shirai, Yukari (Almost Everything, 2022)
How to Embroider Almost Every Cute Thing offers an amazing array of supercute, sweet, charming, and just plain adorable motifs for embellishing fashion and home decor.